(untitled) (Journal of Pharma Insights and Research, 2024)
Allamanda cathartica, a perennial shrub of the Apocynaceae family, has garnered significant attention in pharmacological research due to its diverse bioactive compounds and potential therapeutic applications. This study aimed to investigate the phytochemical composition and evaluate the in vitro antimitotic activity of A. cathartica methanolic extract. Comprehensive phytochemical screening revealed the presence of carbohydrates, alkaloids, saponin glycosides, proteins, tannins, flavonoids, and amino acids in the extract. The antimitotic potential was assessed using a seed germination assay with Vigna radiata L. (green gram) seeds. The methanolic extract exhibited dose-dependent growth inhibition, with 100 μg/mL concentration demonstrating complete inhibition comparable to the standard drug methotrexate. At lower concentrations of 25 μg/mL and 50 μg/mL, the extract showed 50% and 65.5% inhibition, respectively. These findings suggest that A. cathartica possesses significant antimitotic properties, potentially attributable to its rich phytochemical profile. The study also highlights the plant’s other pharmacological activities, including antioxidant, anti-inflammatory, wound healing, and antimicrobial properties. Given the growing interest in natural products for cancer therapeutics, A. cathartica presents a promising candidate for further investigation